2015
DOI: 10.1353/gpr.2015.0011
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Use of Wild Fruits by the Lakota in South Dakota and Implications for Cultural Identity

Abstract: We present modern-day uses of traditionally used wild fruits among the Lakota on Rosebud Reservation as determined from interviews conducted in 2012. We quantify modern-day uses of wild fruits for food, beverages, tonics, medicines (physical and/or spiritual), and crafts. Use of buffaloberries, buffalo currants, chokecherries, riverbank grapes, plums, rosehips, and other plant parts remain as customs among the Lakota although the knowledge and practice of using wild fruits may be waning. Many interviewees impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Chokecherry is a popular berry within the study area, found within a diversity of edible products. It has also been used as a medicine by the Anishinaabe and Lakota people (Densmore, 1974; Kant et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Chokecherry is a popular berry within the study area, found within a diversity of edible products. It has also been used as a medicine by the Anishinaabe and Lakota people (Densmore, 1974; Kant et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, slightly more than half (54%) of the non‐domesticated herbaceous plants included in the calendars are consumed. Of all herbaceous plants, the most frequently mentioned (included in all seven calendars) was prairie turnip ( thíŋpsiŋla or thípsiŋna , Psoralea esculenta ), a non‐domesticated native legume that produces nutritious root nodules used in Dakota and Lakota foodways (Kant et al., 2015 ; Ruelle & Kassam, 2011 ; Stahnke et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…We hope the results described in this manuscript provide enhanced motivation for continued progress toward food sovereignty. Traditional food and foodways foster a sense of connection to the community, the past, and the land for many Indigenous Peoples (Kant et al, 2015;Pufall et al, 2011;Samson & Pretty, 2006;Willows, 2005). They are also ways of restoring and maintaining traditional knowledge about food and the land that is being lost.…”
Section: Resultsmentioning
confidence: 99%